Non-basal dislocations should be accounted for in simulating ice mass flow - Chauve, T.; Montagnat, M.; Piazolo, S.; Journaux, B.; Wheeler, J.; Barou, F.; Mainprice, D.; Tommasi, Andrea (Earth and Planetary Science Letters, 2017)
International audience Prediction of ice mass flow and associated dynamics is pivotal at a time of climate change. Ice flow is dominantly accommodated by the motion of crystal defects-the dislocations. In the specific case of ice, their observation is not always accessible by means of the classical tools such as X-ray diffraction or transmission electron microscopy (TEM). Part of the dislocation population, the geometrically necessary dislocations (GNDs) can nevertheless be constrained using crystal orientation measurements via electron backscattering diffraction (EBSD) associated with appropriate analyses based on the Nye (1950) approach. The present study uses the Weighted Burgers Vectors, a reduced formulation of the Nye theory that enables the characterization of GNDs. Applied to ice, this method documents, for the first time, the presence of dislocations with non-basal [c] or < c+a > Burgers vectors. These [c] or < c+a > dislocations represent up to 35% of the GNDs observed in laboratory-deformed ice samples. Our findings offer a more complex and comprehensive picture of the key plasticity processes responsible for polycrystalline ice creep and provide better constraints on the constitutive mechanical laws implemented in ice sheet flow models used to predict the response of Earth ice masses to climate change.